Statistics at the zoo. Issue 5 (29th September 2020) - Holmes, Lisa; Edwards, Katie; Moss, Andy; Tollington, Simon; Fowler, Anna; Hughes, David; Sudell, Maria
Abstract : At Chester Zoo, it is not only the keepers who are taking care of the animals. Statistical methods are used to promote animal welfare and to preserve and protect endangered species. Abstract : At Chester Zoo, it is not only the keepers who are taking care of the animals. Statistical methods are used to promote animal welfare and to preserve and protect endangered species. By Lisa Holmes, Katie Edwards, Andy Moss, Simon Tollington, Anna Fowler, David Hughes and Maria Sudell.